Developmental Characterization of Schizophrenia-Associated Gene Zswim6 in Mouse Forebrain - Chang, Chuan-Chie; Kuo, Hsiao-Ying; Chen, Shih-Yun; Lin, Wan-Ting; Lu, Kuan-Ming; Saito, Tetsuichiro; Liu, Fu-Chin (Frontiers in Neuroanatomy, 2021)
Schizophrenia is a devastating neuropsychiatric disease with a globally 1% life-long prevalence. Clinical studies have linked ZSWIM6 mutations to developmental and neurological diseases, including schizophrenia. ZSWIM6 function remains largely unknown. Given the involvement of ZSWIM6 in schizophrenia and schizophrenia as a neurodevelopmental disease, it is important to understand the spatiotemporal expression pattern of ZSWIM6 in the developing brain. Here, we performed a comprehensive analysis of the spatiotemporal expression pattern of Zswim6 in the mouse forebrain by in situ hybridization with radioactive- and non-radioactive-labeled riboprobes. Zswim6 mRNA was detected as early as E11.5 in the ventral forebrain. At E11.5-E13.5, Zswim6 was highly expressed in the lateral ganglionic eminence (LGE). The LGE consisted of two progenitor populations. Dlx+;Er81+ cells in dorsal LGE comprised progenitors of olfactory bulb interneurons, whereas Dlx+;Isl1+ progenitors in ventral LGE gave rise to striatal projection neurons. Zswim6 was not colocalized with Er81 in dorsal LGE. In ventral LGE, Zswim6 was colocalized with striatal progenitor marker Nolz-1. Zswim6 was highly expressed in the subventricular zone (SVZ) of LGE in which progenitors undergo the transition from proliferation to differentiation. Double labeling showed that Zswim6 was not colocalized with proliferation marker Ki67 but was colocalized with differentiation marker Tuj1 in the SVZ, suggesting Zswim6 expression in early differentiating neurons. Zswim6 was also expressed in the adjacent structures of medial and caudal ganglionic eminences (MGE, CGE) that contained progenitors of cortical interneurons. At E15.5 and E17.5, Zswim6 was expressed in several key brain regions that were involved in the pathogenesis of schizophrenia, including the striatum, cerebral cortex, hippocampus, and medial habenular nucleus. Zswim6 was persistently expressed in the postnatal brain. Cell type analysis indicated that Zswim6 mRNA was colocalized with D1R-expressing striatonigral and D2R-expressing striatopallidal neurons of the adult striatum with a higher colocalization in striatopallidal neurons. These findings are of particular interest as striatal dopamine D2 receptors are known to be involved in the pathophysiology of schizophrenia. In summary, the comprehensive analysis provides an anatomical framework for the study of ZSWIM6 function and ZSWIM6-associated neurological disorders.